Perspectives of Pregnant Women Regarding Iron Deficiency Anemia - Sirikanok Klankhajhon; Kornkarn Pansuwan; Kanokon Klayjan; Nannaphat Nensat (Universitas Airlangga, 2021)
Introduction: Iron deficiency anemia (IDA) is a global health problem. The prevalence of anemia in pregnancy worldwide is nearly half of pregnant women. It impacts on women and offspring outcomes during pregnancy, intrapartum and postpartum period associated with increasing rate of preterm labor, pregnancy induced hypertension, low birth weight, perinatal death including postpartum hemorrhage, postpartum infection, unsuccessful rate of exclusive breast feeding, and postpartum depression. Inadequate iron intake, maternal physiological changes during pregnancy, and bleeding were indicated as common causes of IDA in pregnancy. The objective was to explore the experiences of pregnant women regarding IDA.Methods: A total of eighteen women between 16-36 weeks gestation participated in the qualitative research. Women were selected by purposive sampling according to inclusion criteria to in-depth interviewed at antenatal care clinic, Watbot hospital, Phitsanulok, Thailand.Results: Thematic analysis of the qualitative interviews identified four main themes: iron-deficiency anemia in pregnant as a normal pregnancy; concern on food rather than hematocrit (Hct) level; maternal instinct in healthy baby; and low socioeconomic as a main obstacle. Conclusion: The findings illustrated to enhance better understanding the nature, attitude, knowledge, perception, and behavior of pregnant women on IDA, facilitators to support women for healthy behavior, and barriers to IDA in pregnancy based on Thai context.